1988
DOI: 10.2214/ajr.151.3.551
|View full text |Cite
|
Sign up to set email alerts
|

Brain MR: pathologic correlation with gross and histopathology. 1. Lacunar infarction and Virchow-Robin spaces

Abstract: MR imaging wasIn contrast, dilated Virchow-Robin spaces were isointense relative to CSF in vivo or to fluid in the subarachnoid space in the postmortem state on all pulse sequences in all four cases. They were round or linear, and in general were smaller than the lacunae, although some overlap in size did occur. They were seen at the level immediately above the bifurcation of the internal carotid into the middle and anterior cerebral arteries and were seen on successive axial sections In the putamen (most prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
161
0
5

Year Published

1990
1990
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(170 citation statements)
references
References 1 publication
(1 reference statement)
4
161
0
5
Order By: Relevance
“…A special MR imaging change of cribriform cavities in the BG was the feature of this group. An "état criblé" or "status cribrosum" has been previously proved to be multiple dVRS in pathologic studies 19 and has been reported only among cases of vascular Parkinsonism, 20 subcortical ischemic vascular dementia, 21,22 or CADASIL 23 but has not been reported in the general population, to our knowledge. The present data further emphasize that the accumulation of multiple dVRS is not rare and can occur in elderly people in the absence of severe disability or dementia.…”
Section: Discussionmentioning
confidence: 77%
“…A special MR imaging change of cribriform cavities in the BG was the feature of this group. An "état criblé" or "status cribrosum" has been previously proved to be multiple dVRS in pathologic studies 19 and has been reported only among cases of vascular Parkinsonism, 20 subcortical ischemic vascular dementia, 21,22 or CADASIL 23 but has not been reported in the general population, to our knowledge. The present data further emphasize that the accumulation of multiple dVRS is not rare and can occur in elderly people in the absence of severe disability or dementia.…”
Section: Discussionmentioning
confidence: 77%
“…Similar to infarcts, on T2-weighted MRI état criblé appear as bright spots, but are said to be smaller than infarctions. A cutoff diameter of 3 mm was adopted according to the guidelines of the Japanese Society for Detection of Asymptomatic Brain Diseases and was also used in some epidemiological studies (21,(45)(46)(47). In reality, however, it is quite difficult to clearly separate the two conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors 13 regard vascular ectasia leading to dilated perivascular spaces as the most likely explanation for most of the lesions, whereas other authors 14 regard mild vascular insufficiency leading to atrophy of the perivascular tissue as the underlying mechanism. Small lacunar infarcts and dilated Virchow-Robin spaces (e~tat cribl6) cannot be distinguished by MRI characteristics 15 ; both are strongly associated with hypertension. 16 All these studies refer to elderly patients, and the pathological basis of the lesions described in our patients may or may not be different, especially because hypertension was not present in our patients.…”
Section: Discussionmentioning
confidence: 99%